Children Out of Bounds The Power of Case Studies in Expanding Visions of Literacy Development - Dyson, Anne Haas.; National Center for the Study of Writing and Literacy, Berkeley, CA.; National Center for the Study of Writing and Literacy, Pittsburgh, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
This paper shows that constructing or writing a case study is a dialogic process, one that requires the researcher to define and redefine his or her research boundaries. The paper elaborates, first, on the process of constructing a case and, second, on the particular process of constructing cases of children learning written language. It highlights the use of interpretive methodologies, such as those of C. Geertz and F. Erickson, to construct cases; such methodologies probe how specific people, in specific social circumstances, interpret or make sense of their everyday interactions. The paper then offers examples of 3 cases written successively over a 15-year period. Collectively, these cases illustrate the methodological dynamics of case studies, the ways in which they may force an observer both to articulate conceptual boundaries and to go beyond them. Finally, in the concluding section, the paper considers the potential for case studies to cross distinctive professional boundaries, so that practitioners with mutual interests can be brought into a common conversation about the young. It also considers the limits imposed on that potential when studies become prescriptive or normative guides. (Contains 59 references and 5 figures.) (TB)
Sponsoring Agency: Spencer Foundation, Chicago, IL.
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: R117G10036.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Case Studies; Childrens Writing; Cooperation; Emergent Literacy; Ethnography; Individual Development; Literacy; Research Methodology; Writing Research; Young Children; Researcher Role; Reports, Research